Within hearing distance? Recent developments in Pentateuch and Chronicles Research - Jonker, Louis C. (Old Testament essays, 2014)
Biblical scholarship suffers from over-specialisation and over-compartmentalisation. For many decades Pentateuch studies as the "queen" of biblical scholarship have dominated the field, and required high levels of specialisation. Although not as dominant as Pentateuch studies, other areas in OT scholarship have also reverted into sub-guilds of scholars only talking to themselves. Recent developments in Pentateuch studies and studies of Persian period literature (such as Chronicles) have resulted into different sub-guilds coming within hearing distance from one another. This article provides an overview of some of these developments.